Analysis of the Ayat Kursi (Qs. Al-Baqarah Verse 255) in Tafsir Muyassar: The Meaning of Monotheism and the Power of Allah - Yolanda Septiani; Uus Husni Hoer; Miftahol Arifin; Salsabila Muthmainah (al-Afkar, Journal For Islamic Studies, 2026)
QS. Al-Baqarah verse 255 (ayat kursi) is one of the greatest verses in the Qur'an because it emphasizes the oneness and power of Allah. Tafsir Muyassar, as one of the concise tafsir compiled by scholars from the King Fahd Mushaf Printing Complex, provides a simple but in-depth explanation of this verse. This journal aims to analyze Tafsir Muyassar's explanation of the Ayat Kursi and its relevance in everyday life. The method used in this research is a literature study with a descriptive-analytical approach. The research results show that Ayat Kursi contains the concept of monotheism, the absolute power of Allah, and the importance of depending on Him. Apart from that, this verse also has the priority of protection from Satan's interference. By understanding Ayat Kursi in depth through Tafsir Muyassar, a Muslim can increase his faith and devotion to Allah.